Effect of moringa flower extract on liver function and histopathology appearance of obesity model rat's liver - Wahyuniasri, Nuri Rahma; Nardi, Leo; Sopacua, Erwin (Program Studi Magister Kesehatan Masyarakat Universitas Prima Indonesia, 2024)
This study aims to test and analyze the effectiveness of moringa flower extract on the liver function of male wistar strain white rats obesity model and how the histopathological picture. This research is a type of experimental quantitative research using post-test only group design. This study used test animals in the form of male white wistar rats with a body weight of 200-300 gr aged 2-3 months. The test animals were divided into 4 groups, the control group was only given regular food and distilled water, the treatment group was given high-fat food and Moringa flower extract at different doses, namely 200 mg / kgBB, 400 mg / kgBB, and 600 mg / kgBB. The results of the phytochemical test showed that moringa flower extract contains secondary metabolites in the form of saponins, tannins, flavonoids, alkaloids, and steroids. The administration of moringa flower extract at a dose of 600 mg/KgBB is effective in improving liver function in obese Wistar white rats. This improvement can be seen through the levels of ALT, AST, and histological structure of the liver that has improved. The results of histopathological observations of liver tissue in treatment group 3, namely moringa flower extract at a dose of 600 mg/KgBB, experienced the most significant improvement and approached the control group compared to other groups.